Saliva glucose test in canine diabetes monitoring - Tukonen, Laura (2024)
Because incidence of diabetes mellitus in dog has increased, easy and efficient glucose monitoring techniques are needed. Saliva sampling offers a straightforward and non-invasive method for measuring glucose levels in dogs, providing a unique way to study disease markers. The low α-amylase levels in canine saliva ensure stable glucose measurements without the need for invasive procedures. This thesis aims to evaluate the effectiveness of the prototype 2 saliva glucose test for monitoring glucose levels in dogs. We compared the saliva test results to simultaneous traditional blood and urine glucose tests and to continue monitoring of interstitial glucose level with a skin-attached electronic device. Additionally, the owners of the dogs gave feedback on the tests’ usability. The Prototype 2 saliva glucose test showed a 71.3% accuracy in a study of 164 samples, with 80.5% sensitivity and 66.6% specificity. Moreover, the saliva test demonstrated moderate discriminative ability, with an Area Under Curve (AUC) value of 0.708. The dogs’ owners feedback revealed high satisfaction with the tests’ non-invasive nature and easy use. The Prototype 2 saliva glucose test has the potential to significantly improve canine diabetes management by offering a less stressful and more accessible monitoring option for pet owners. But this test still needs further development.